2022
DOI: 10.3390/md20070413
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fine Dust Effect of Fucoidan Extracted from Ecklonia maxima Leaves in Macrophages via Inhibiting Inflammatory Signaling Pathways

Abstract: Brown seaweeds contain fucoidan, which has numerous biological activities. Here, the anti-fine-dust activity of fucoidan extracted from Ecklonia maxima, an abundant brown seaweed from South Africa, was explored. Fourier transmittance infrared spectroscopy, high-performance anion-exchange chromatography with pulsed amperometric detection analysis of the monosaccharide content, and nuclear magnetic resonance were used for the structural characterization of the polysaccharides. The toll-like receptor (TLR)-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…Interestingly, the extracts with lower molecular weights showed strongest effects in this study, indicating an influence of molecular weight on the anti-inflammatory activity of fucoidans [ 86 ]. Nonetheless, Nagahawatta et al observed that fucoidans from Ecklonia maxima with similar molecular weights to those reported in the later study but higher sulfate contents than other extracts showed the best anti-inflammatory effect by attenuating TLR-mediated NF-κB/MAPK signaling [ 81 ].…”
Section: Mechanisms Of Fucoidan Actionsmentioning
confidence: 82%
See 2 more Smart Citations
“…Interestingly, the extracts with lower molecular weights showed strongest effects in this study, indicating an influence of molecular weight on the anti-inflammatory activity of fucoidans [ 86 ]. Nonetheless, Nagahawatta et al observed that fucoidans from Ecklonia maxima with similar molecular weights to those reported in the later study but higher sulfate contents than other extracts showed the best anti-inflammatory effect by attenuating TLR-mediated NF-κB/MAPK signaling [ 81 ].…”
Section: Mechanisms Of Fucoidan Actionsmentioning
confidence: 82%
“…These molecules play an important role in several cellular functions, but also up-regulate inflammatory responses inducing NF-κB activation and secretion of pro-inflammatory cytokines [ 78 , 79 ]. Several studies have reported that fucoidans isolated from brown seaweeds have the potential to inhibit MAPK phosphorylation [ 65 , 80 , 81 ]. Fucoidans obtained from Saccharina japonica demonstrated anti-inflammatory effects in vivo and in vitro in macrophages through the downregulation of MAPK expression (such as p38, ENK, and JNK) and NF-κB (such as p65 and IKKα/IKKβ) signaling pathways [ 33 ].…”
Section: Mechanisms Of Fucoidan Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified fucoidan fraction from T. ornate down-regulated iNOS, COX-2, and pro-inflammatory cytokines, including PGE2 levels in RAW 264.7 macrophages [ 14 ]. Purified fucoidan from Ecklonia maxima (fucose content 81%) reduced prostaglandin E2, NO, and pro-inflammatory cytokines, such as TNF-α, IL-6, and IL-1β in macrophages [ 18 ]. A fucoidan from brown algae A. nodosum inhibited poly(I:C)-induced expression of some cytokines [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inflammatory activity can be suppressed by inhibiting protein denaturation [ 14 ]. Although several anti-inflammatory mechanisms of fucoidan were reported [ 15 , 16 , 17 , 18 ], very little is known about the ability of fucoidans to prevent protein denaturation. Agents that can prevent protein denaturation would be worthwhile for anti-inflammatory drug development.…”
Section: Introductionmentioning
confidence: 99%